ANALISIS SEMIOTIKA PADA MANTRA BANJAR DI DESA TELUK KEPAYANG - Normasunah - (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2016)
The method used in this research is descriptive method kualitatif.Dengan descriptive qualitative method will be described overall results of the analysis in the form of symbols and meanings semiotics at Banjar mantra in the village of Teluk Kepayang. With the steps of collecting, managing, analyzing, and presenting data with interview and observation techniques. Based on the results penelitianPada Banjar spell Teluk Kepayang found some symbols In Banjar spells Teluk Kepayang found some symbols are: a symbol of confidence, a symbol binder. a symbol of health and hygiene, and symbols perlindungan.Dalam Banjar mantra meaning there are four sections covering: a title that reflects part of the purpose of the spell in question, part of the sentence Opener basmalah used to open an action so that such acts receive a blessing from God Almighty, the base or description, contains words which have the potential to spell someone unseen, part of the purpose, an expectation to be achieved, cover, namely sentences diucapakan to end the spell that had given two creed sentence. Keywords: Semiotics, Mantra Banjar